PENGARUH KUALITAS PRODUK, CITRA MEREK DAN PERSEPSI HARGA TERHADAP PROSES KEPUTUSAN PEMBELIAN KONSUMEN SEPEDA MOTOR MATIC âHONDAâ - Nurul Fatmawati. A, 12.05.51.0085 (Students Journal of Economic and Management, 2016)
The purpose of this study was to analyze the effect of product quality, brand image and perception of the price of the consumer buying decision process matic Honda motorcycles. The population in this study were matic Honda motorcycle users. The samples in this study using purposive sampling, which means that sample based on specific criteria, namely: those who are older and those who use and have matic Honda motorcycles. The analytical tool used is multiple linear regression analysis. The results of the analysis can be concluded that: product quality, positive influence on consumer buying decision process matic Honda motorcycles. Brand image positive influence on consumer buying decision process matic Honda motorcycles. Perception price positive influence on consumer buying decision process matic Honda motorcycles. Â  Keywords: product quality, brand image, perception of price and consumer purchase decision process